2019
DOI: 10.1002/acm2.12755
|View full text |Cite
|
Sign up to set email alerts
|

Intrafraction 4D‐cone beam CT acquired during volumetric arc radiotherapy delivery: kV parameter optimization and 4D motion accuracy for lung stereotactic body radiotherapy (SBRT) patients

Abstract: PurposeElekta XVI 5.0 allows for four‐dimensional cone beam computed tomography (4D CBCT) image acquisition during treatment delivery to monitor intrafraction motion. These images can have poorer image quality due to undersampling of kV projections and treatment beam MV scatter effects. We determine if a universal intrafraction preset can be used for stereotactic body radiotherapy (SBRT) lung patients and validate the accuracy of target motion characterized by XVI intrafraction 4D CBCT.MethodsThe most critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…For smaller lung targets, the target localization may be more affected by the MV treatment scatter artifacts. Although it was demonstrated that the lung target in the XSight tracking phantom was localized with sub-millimeter accuracy, similar to the results in a recent study [20], target localization accuracy may be lower in patient cases.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…For smaller lung targets, the target localization may be more affected by the MV treatment scatter artifacts. Although it was demonstrated that the lung target in the XSight tracking phantom was localized with sub-millimeter accuracy, similar to the results in a recent study [20], target localization accuracy may be lower in patient cases.…”
Section: Discussionsupporting
confidence: 82%
“…Consequently, the number of projections acquired for the in-treatment CBCT could vary depending on the VMAT plans delivered with the CBCT acquisition. Instead of defining the gantry speed, an angular interval, so called the acquisition interval in XVI, was defined for acquiring the in-treatment CBCT; the acquisition interval is an acquisition parameter that defines the minimum gantry rotation, upon which kV projection acquisition is triggered (0.1° for this study as suggested in a previous study [ 20 ]). As summarized in Table 1 , more projections were acquired for the three-dimensional (3D) in-treatment CBCT than the 3D pretreatment CBCT: 495 vs. 333 projections.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[301][302][303][304][305] Despite the aforementioned challenges, researchers have done a tremendous amount of work to address these issues, and 4D-CBCT has been shown to be of important clinical utility. Multiple studies have reported superior target visualization and increased confidence in ITV localization with 4D-CBCT technology, thereby recommending it as a more accurate image-guidance technique for moving targets as compared to 3D-CBCT, [306][307][308][309][310][311] even improving the interobserver variability. 312 Four dimensional CBCT was shown to result in dosimetric advantages via the ability to reduce margins and thus irradiate less normal tissue, 313 as well as facilitating accurate verification of target position for both inter-and intra-fractional motion for lung SBRT with VMAT delivery.…”
Section: B Investigated Solutionsmentioning
confidence: 99%
“…Determining where an image is binned in the respiratory cycle is based on the position of high-contrast anatomical landmarks such as the diaphragm in each image. [8][9][10] After the images are binned, a 3D CBCT is reconstructed for each phase of the respiratory cycle, where the typical number of phases is 10. The 4D CBCT allows for accurate visualization of the tumor in each phase of the respiratory cycle by reducing motion artifacts associated with traditional 3D CBCT imaging acquisitions.…”
Section: Introductionmentioning
confidence: 99%